Transforming Curriculum Design with Generative AI: A Model for Assessing Teacher Digital Competence. - Guillén Gámez, Francisco David; Tomczyk, Łukasz; Habibi, Akhmad; Díaz Vargas, Bethy Linoska (Springer, 2026)
This dataset contains the responses collected from teachers through a structured questionnaire designed to analyse their perceptions, attitudes, and behavioural intentions regarding the use of Generative Artificial Intelligence (GenAI) tools in educational contexts. The dataset includes sociodemographic variables and questionnaire items measured using Likert-type scales.
Keywords: Tecnología educativa; Alfabetización digital; Inteligencia artificial en la enseñanza; Currículo educativo - Planificación; Curriculum planning; Artificial Intelligence; Teacher competence; TAM; Digital competence; Education technology; GenAI